Applying mathematics : immersion, inference, interpretation - Bueno, Otávio; French, Steven (Oxford University Press, 2018)
How is that when scientists need some piece of mathematics through which to frame their theory, it is there to hand? Bueno and French offer a new approach to the puzzle of the applicability of mathematics, through a detailed examination of a series of case studies from the history of twentieth-century physics.